Review Study of Non-Forced Convection Heat Transfer Inside Enclosures with Different Enhancement Techniques and Configurations - Ahmed Ali, Sarmad (Journal of Advanced Industrial Technology and Application, 2025)
Many industrial engineering applications such as thermal storage plants, solar energy, cooling in reactors, microelectronic electrical systems, and gas-insulated electrical systems use natural convection heat transfer represented by the principle of heat transfer from the heating source to the cold ambient or cold cavity wall. The function of the outer surface of the cavity is to protect the body inside the cavity in the harsh external environment by also reducing the heat transfer process from the hot inner surface. On this topic, many researchers conducted their previous studies and literary investigations using various methods to enhance heat transfer by natural convection, such as mixing nanomaterials with water or inserting porous materials into various configurations to increase the coefficient of thermal conductivity of the main working fluid. Other methods have been applied, for example, vibration, Rayleigh numbers, boundary conditions, magnetic field, or changing the geometry of the cavity composition. The current research aims to study heat transfer by natural convection inside cavities of various configurations, including square, non-square, triangle, and rectangle, in addition to addressing ways to enhance heat transfer, the most important nanofluid and porous medium.